2016
DOI: 10.1515/revce-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification in inorganic filler of mixed matrix membrane for enhancing the gas separation performance

Abstract: AbstractThe development of mixed matrix membrane (MMM) in gas separation process has drawn great attention due to its promising properties. MMM consists of a polymer as the matrix phase, whereas the inorganic filler serves as the dispersed phase. However, poor contact between these two phases often results in unselective gas flow and becomes one of the major issues in the MMM development. Currently, various modification techniques of the inorganic filler to improve the compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 101 publications
0
29
0
Order By: Relevance
“…. In general, hydroxyl groups are present on the alumina surface: these groups react with the ethoxy group of APTES under high temperature to form a covalent bond between the APTES and alumina . Meanwhile, the amine group in the APTES molecule allows it to react with the dianhydride group of polyimide .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. In general, hydroxyl groups are present on the alumina surface: these groups react with the ethoxy group of APTES under high temperature to form a covalent bond between the APTES and alumina . Meanwhile, the amine group in the APTES molecule allows it to react with the dianhydride group of polyimide .…”
Section: Resultsmentioning
confidence: 99%
“…In general, hydroxyl groups are present on the alumina surface: 38,39 these groups react with the ethoxy group of APTES under high temperature to form a covalent bond between the APTES and alumina. 40 Meanwhile, the amine group in the APTES molecule allows it to react with the dianhydride group of polyimide. 41 The formation of covalent bond between the APTES, alumina and polyimide enhanced their affinity to each other and hence stabilized the membrane system.…”
Section: Formation Of Defect-free Polyimide Base Layermentioning
confidence: 99%
“…TiO 2 nanoparticles were functionalized by EDA by following the methodology by Venna and Carreon and Ahmed et al . with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Literature reported that surface modification of inorganic filler using amine compounds has become an encouraging approach to enhance the poor adhesion concern in MMMs . Venna and Carreon, reported that incorporating organic amino cations such as ethylenediamine (EDA) in SAPO‐34 membranes resulted in a 40% higher separation index of CO 2 /CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…MMMs are heterogeneous membranes with the combination of inorganic materials, reinforced in the continuous polymeric matrix. Researchers reported extensive work on MMMs . Powell et al reported that the addition of nanoparticles mainly can contribute three effects to the membrane permeability, i.e., they can act as molecular sieves to change the permeability, they can alter the membrane matrix structure to enhance the permeability, and they can also work as a wall to decrease the permeability.…”
Section: Applications Of Ils In Gas Separation Membranesmentioning
confidence: 99%